A Philological Study of The Tanjung Barulak Tarekat Manuscript in Arabic and Pegon Arabic - Hanif, Akhyar; Afrina, Cut; Rudiamon, Septika; Mudinillah, Adam; Deswita, Deswita; Rahmi, Elvi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This paper aims to analyze the text in the Tanjung Barulak Sufi manuscript, Tanah Datar district. This study uses a philological research method with the object of study being a manuscript with the code 02/BB.II/twf/2021. This method has six working steps: manuscript inventory, manuscript description, manuscript grouping and comparison, selection of text edition methods, transliteration, and additional studies. This study reveals four main teachings of the Naqsyabandiyah Sufi order, first, absolute obedience to the teacher based on the terminology of the text